A gas chromatography/pyrolysis/isotope ratio mass spectrometry system for high-precision δD measurements of atmospheric methane extracted from ice cores - Bock, Michael; Schmitt, Jochen; Behrens, Melanie; Möller, Lars; Schneider, Robert; Sapart, Celia; Fischer, Hubertus (Rapid Communications in Mass Spectrometry, 2010)
Air enclosures in polar ice cores represent the only direct paleoatmospheric archive. Analysis of the entrapped air provides clues to the climate system of the past in decadal to centennial resolution. A wealth of information has been gained from measurements of concentrations of greenhouse gases; however, little is known about their isotopic composition. In particular, stable isotopologues (δD and δ13C) of methane (CH4) record valuable information on its global cycle as the different sources exhibit distinct carbon and hydrogen isotopic composition. However, CH4 isotope analysis is limited by the large sample size required and the demanding analysis as high precision is required. Here we present a highly automated, high-precision online gas chromatography/pyrolysis/isotope ratio monitoring mass spectrometry (GC/P/irmMS) technique for the analysis of δD(CH4). It includes gas extraction from ice, preconcentration, gas chromatographic separation and pyrolysis of CH4 from roughly 500 g of ice with CH4 concentrations as low as 350 ppbv. Ice samples with approximately 40 mL air and only ∼1 nmol CH4 can be measured with a precision of 3.4‰. The precision for 65 mL air samples with recent atmospheric concentration is 1.5‰. The CH4 concentration can be obtained along with isotope data which is crucial for reporting ice core data on matched time scales and enables us to detect flaws in the measurement procedure. Custom-made script-based processing of MS raw and peak data enhance the system's performance with respect to stability, peak size dependency, hence precision and accuracy and last but not least time requirement.